2018
DOI: 10.24996/ijs.2018.59.3a.7
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and clinical study of leishmaniasis in Kirkuk city, Iraq

Abstract: leishmaniasis is a disease of global concern, Leishmania types and distribution rates vary from country to another. For visceral leishmaniasis serum samples were examined by the kala-azar dipstick rapid test. Meanwhile smears were taken from lesions, air dried, fixed and Leishman stained then microscopically examined for amstigote stage in cutaneous leishmaniasis. From April 2014 to April 2015, 150 samples for cutaneous leishmaniasis (CL) and 108 serum sample for visceral leishmaniasis (VL) from in and out pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…The authors attributed this result to the weakness of children's immune system as compared to that of the adults, or the exposure to low doses of the parasite transmitted by sandflies. Furthermore, the results of the present study agree with those of another study [22], which found that the overall incidence of CL is greater among people who are 5-14 years old. This age is the school and work age in Iraq for both genders, who are more likely to participate in outdoor activities and be exposed to sandfly-associated environmental conditions.…”
Section: Resultssupporting
confidence: 92%
“…The authors attributed this result to the weakness of children's immune system as compared to that of the adults, or the exposure to low doses of the parasite transmitted by sandflies. Furthermore, the results of the present study agree with those of another study [22], which found that the overall incidence of CL is greater among people who are 5-14 years old. This age is the school and work age in Iraq for both genders, who are more likely to participate in outdoor activities and be exposed to sandfly-associated environmental conditions.…”
Section: Resultssupporting
confidence: 92%